Lessons learned in nutrition therapy in patients with severe COVID-19 (2021)
The coronavirus disease 2019 (COVID‐19) pandemic has reached worldwide, and until a vaccine is found, it will continue to cause significant morbidity and mortality. The clinical presentation of COVID‐19 ranges from that of being asymptomatic to developing a fatal illness characterized by multiple organ involvement. Approximately 20% of the patients will require hospitalization; one‐quarter of hospitalized patients will develop severe COVID‐19 requiring admission to the intensive care unit, most frequently, with acute respiratory failure. An ongoing effort is being made to identify the patients that will develop severe COVID‐19. Overall, patients present with 3 different phenotypes of nutrition risk: (1) the frail older patient, (2) the patient with severe ongoing chronic illness, and (3) the patient with severe and morbid obesity. These 3 phenotypes represent different nutrition risks and diverse nutrition interventions. This article explores the different potential approaches to nutrition intervention in patients with COVID‐19, evaluating, in this process, the challenges faced in the implementation of guidelines written by different societies.